THE USE OF THE CONSTRUCTION SIMA VILLAGE AS AN NEW CONTRUCTION OF RULES - Purweni Widhianningrum (Universitas Airlangga, 2022)
This study seeks to understand and construct the concept of financial governance that has been practiced in sîma village by using a hermeneutic approach. Various written sources that have relevance to the research topic are used as a source of data analysis in this study. The results show that the beliefs of the ancient Javanese community through their holistic knowledge of the cosmological reality also influenced the structuring of the sîma village to its core, namely financial management. The concept of cosmology refers to the importance of wisdom in carrying out all life activities by maintaining a balance between worldly and spiritual life. The idea of financial governance in the same village, especially regarding the policy of allocating income to the village, has the same concept as the Village Law. Villages are given autonomous authority by the kingdom to manage the potential of their resources, including revenue and allocation of regional cash expenditures. The allocation of expenditure for the sîma village is prioritized on the maintenance and management of sacred buildings. The development of village infrastructure is specifically directed at development efforts that support people's agricultural businesses, such as the construction of dams as flood control, provision of adequate agricultural technology, irrigation systems, pest control and post-harvest handling. The wisdom of managing the sîma village finances in the past had implications for humans to think with perfect reason and behave according to the heart to create peace, prosperity, and the continuity of life for all the inhabitants of the universe.